Local and global sensitivity analysis of key durability parameters of concrete under chloride environment - Lingjie Wu; Chengjian Yu; Fenfei Shi; Xuping Ni (Results in Engineering)
This study investigates the local and global sensitivity of five critical durability parameters affecting concrete performance in chloride environments: concrete cover thickness (d), apparent chloride diffusion coefficient (Dₐₚₚ), surface chloride concentration (Cₛ), critical chloride concentration (Ccr), and age factor (m) for characterizing the time-dependent decay of Dₐₚₚ. By integrating the One-At-a-Time (OAT) method for local sensitivity analysis with the extended Fourier Amplitude Sensitivity Test (EFAST) and Sobol methods for global sensitivity analysis, a systematic evaluation is conducted to identify distinct influence mechanisms of these parameters under deterministic and time-dependent durability life prediction models. Results demonstrate that parameter distribution functions and coefficients of variation (COV) significantly alter sensitivity outcomes, with parameter interactions amplifying or mitigating individual effects. Notably, d emerges as the dominant parameter governing concrete durability life, with its sensitivity enhanced by COV variations and synergistic interactions with Dₐₚₚ and Cₛ. Global sensitivity analysis reveals that d and Dₐₚₚ exhibit the strongest interaction (contributing 58.5 % of total second-order interactions in Sobol and 115 % higher total interaction effects in EFAST), underscoring their coupled influence on chloride transport kinetics. While the OAT method yields conservative sensitivity estimates by neglecting interactions, the EFAST and Sobol methods quantify higher-order nonlinear coupling effects, with EFAST showing superior computational efficiency and interaction resolution. The deterministic model aligns with time-dependent model results but overestimates Dₐₚₚ sensitivity due to simplified interaction assumptions.